18-Fluorine-labelled 2-deoxy-2-fluoro-d-glucose positron emission tomography/computed tomography standardised uptake values: a non-invasive biomarker for the risk of metastasis from choroidal melanoma. Issue 10 (12th July 2006) - Finger, P T; Chin, K; Iacob, C E
Abstract : Aims: To correlate the clinical, ultrasound and pathological features of the eyes first evaluated by 18-fluorine-labelled 2-deoxy-2-fluoro-d -glucose (FDG) positron emission tomography (PET)/computed tomography and then enucleated for choroidal melanoma. Methods: 14 consecutive patients enucleated for choroidal melanoma were examined. At presentation, clinical, ultrasound and PET/computed tomography imaging were carried out. Ultrasound was used to measure the tumour size and evaluate the tumour shape and intrinsic vascularity (blood flow). Histopathological and immunohistochemical evaluations included tumour cell type, necrosis, glycogen content, vascularity and extrascleral extension. Results: 13 tumours were T3 and one T2 (American Joint Committee on Cancer – International Union against Cancer). The mean tumour height was 10.6 (range 3.5–17.7) mm with a largest basal dimension of 19.3 (range 14.5–30) mm. Patients having melanoma with the highest six standardised uptake values ((SUV) ⩾4.0) were (on average) >10 years older, their melanomas had larger basal dimensions and were epithelioid-cell type; three melanomas were centred anterior to the equator; three contained enlarged blood vessels (>150 μm in diameter); and three formed extrascleral extension. Patients with the two highest SUV tumours died due to metastatic melanoma. Conclusion: PET/computed tomography imaging offers a physiological assessment of glucose metabolism in primary choroidal melanomas. Increased FDG PET/computed tomography SUV was positively correlated with known clinical, pathological and ultrasound features linked to metastatic potential of choroidal melanoma.